Quo vadis Polish-Canadian writing? Reflections on home, language, writing, and memory in recent texts by Canadian writers of Polish origins - Drewniak, Dagmara (My University, 2020)
The aim of this paper is to look at the recent publications by writers of Polish extraction living in Canada and writing in English in order to examine these texts in the context of their treatment of the concept of home, attitude to mother tongue and the usage of English, as well as the authors’ involvement in shaping the Canadian literary scene. The analysis will concentrate on selected texts published after 2014 to delineate the latest tendencies in Polish-Canadian writing. The discussion will include life writing genres such as memoirs, short stories, and novels. Since these writers have undertaken themes of (up)rootedness, identity, and memory and they have touched upon the creative redefinition of the figure of home, these aspects will also be examined from a theoretical perspective in the introductory part of the article. Steven Tötösy de Zepetnek through his concept of “in-between peripherality” (2010: 87) proposes to view Central and Eastern European literature as both peripheral and in-between its “own national cultural self-referentiality and the cultural influence and primacy of the major Western cultures” (2010: 87). Moreover, as diasporic studies are inspired by the search for transcultural, dynamic exchanges and hybridity (Agnew 2005), the analysis will also include discussions on hybridity understood as a transgression of borders, both literary and genealogical as well as thematic. That is why, the classic notion of hybridity known widely in postcolonial studies, is here understood, according to Moslund (2010), as having horizontal and vertical orientations, where the former designates transgression of borders and space and the latter is connected to the movement across time. This approach is particularly interesting in the context of Polish-Canadian migrant and diasporic literature as, according to Pieterse (2001), hybridity understood as movement and translocation can offer new perspectives on migrant literatures in multi-and transcultural worlds.
Keywords: Canadian writers of Polish origins; Polish-Canadian writing; diasporic writing; home; hybridity